Coagulation defects in thalassemic patients - Mostafa M. Abosdera; Alzahraa E. Almasry; Ehab S. Abdel-Moneim (Elsevier, 2017)
Regular blood transfusion and compliance with iron chelation therapy has markedly improved life expectancy in thalassemia; however, this improvement is accompanied by several complications of this chronic disease including thromboembolic disorders. The objective of this work is to study natural coagulation inhibition as well as the fibrinolysis processes in thalassemic children who are otherwise in a steady state with no overt clinical manifestations of thromboembolism. Methods: In a case-control study design conducted at Sohag University Hospital, Sohag, Egypt, 50 thalassemic children and 20 age- and sex-matched healthy controls were compared as regards prothrombin concentration, international normalized ratio, partial thromboplastin time, protein C, protein S, antithrombin III, D-dimers, and thrombin activatable fibrinolysis inhibitor (TAFI). Results: When compared to healthy controls, natural coagulation inhibitors (protein C, protein S, and antithrombin-III) were significantly lower in thalassemic children (p < 0.0001). While D-dimers showed a significant increase in thalassemic children, TAFI was significantly lower (p < 0.0001). Splenectomized thalassemic children showed significantly lower levels of protein C, protein S and TAFI (p < 0.001, p < 0.0001, p < 0.0001, respectively) when compared to nonsplenectomized thalassemic children. Conclusion: Significant changes in natural coagulation inhibition and fibrinolysis processes favoring thromboembolism can be detected in otherwise healthy thalassemic children. Because these changes are more pronounced in splenectomized patients, study of primary prophylactic strategies in this subgroup is warranted.